Exchange Rate Regimes and the Stability of the International Monetary System - Ghosh, Atish (Occasional Papers; Occasional Paper ;, 2011)
The member countries of the International Monetary Fund collaborate to try to assure orderly exchange arrangements and promote a stable system of exchange rates, recognizing that the essential purpose of the international monetary system is to facilitate the exchange of goods, services, and capital, and to sustain sound economic growth. The paper reviews the stability of the overall system of exchange rates by examining macroeconomic performance (inflation, growth, crises) under alternative exchange rate regimes; implications of exchange rate regime choice for interaction with the rest of the system (external adjustment, trade integration, capital flows); and potential sources of stress to the international monetary system.